Unleashing the power of responsible knowledge management: A catalyst for sustainable business transformation - Raysa Geaquinto Rocha; Arminda Paço; Helena Alves; Cristina Dias-Cabral (Knowledge Management & E-Learning: An International Journal)
This study examines the impact of employees’ knowledge and competencies on the development of sustainable businesses through the lens of responsible knowledge management. We conducted a multinomial logistic regression using Flash Eurobarometer data to analyze the relationships among knowledge, competencies, and sustainability-related actions in the context of companies’ strategies and action plans. Our findings reveal that the absence of employees’ knowledge/competencies impedes the development of sustainable strategies. Additionally, isolated actions such as evaluation of the company’s impact on society, sustainable product or service development, and actions to save energy or switch to sustainable energy sources have a greater impact on the development of sustainable businesses than actions for involving employees in the management and actions to reduce impact or consumption on natural resources. Conversely, reuse or recycling actions have no significant impact. Thus, this research confirms and highlights the need for companies to prioritize knowledge management practices that incorporate sustainability-related competencies. By adopting a values-driven approach to knowledge management, organizations can unlock new avenues for growth, innovation, and competitive advantage while contributing to the larger goal of achieving sustainability. The contributions comprise providing empirical evidence supporting responsible knowledge management development and advancing with the convergence of a reframed knowledge management field and sustainability.